Associations of daily step count with all-cause mortality and cardiovascular mortality in hypertensive US adults: a cohort study from NHANES 2005–2006 - Tuo Guo; Yang Zhou; Guifang Yang; Aifang Zhong; Xiaogao Pan; Yuting Pu; Michael Simons; Lijuan Sheng; Xiangping Chai (BMC Public Health)
Abstract Background The health benefits of physical activity, including walking, are well-established, but the relationship between daily step count and mortality in hypertensive populations remains underexplored. This study investigates the association between daily step count and both all-cause and cardiovascular mortality in hypertensive American adults. Methods We used data from the National Health and Nutrition Examination Survey 2005–2006, including 1,629 hypertensive participants with accelerometer-measured step counts. Cox proportional hazards models and restricted cubic spline regression were employed to assess the associations between daily step count and mortality outcomes. Analyses were adjusted for demographics, lifestyle factors, and comorbidities. Results Over an average follow-up of 12.57 years, 370 deaths occurred, of which 177 were due to cardiovascular causes. We observed non-linear associations between daily step count and mortality. Mortality risks were significantly reduced with step counts to 8,250 steps/day for all-cause mortality and 9,700 steps/day for cardiovascular mortality. Beyond these thresholds, the benefits plateaued. Conclusion Increasing daily step count is associated with reduced all-cause and cardiovascular mortality in hypertensive individuals, with optimal benefits observed below 8,250 and 9,700 daily steps, respectively. Moderate levels of physical activity provide substantial health benefits, highlighting the importance of setting realistic and attainable activity goals for hypertensive populations.